Petrogenesis of the Kanker Granites From the Bastar Craton: Implications for Crustal Growth and Evolution During the Archean-Proterozoic Transition - Asokan, Ajay Dev; Elangovan, R.; Vishwakarma, Neeraj; Hari, K. R.; Ram Mohan, M. (Frontiers in Earth Science, 2020)
Archean-Proterozoic boundary represents a significant transitional phase in the Earth’s history. Bastar Craton is one of the major Archean cratons in the Indian subcontinent with voluminous granites, supracrustal rocks and tectonic belts. Malanjkhand, Dongargarh, and Kanker are the three major granitic plutons emplaced during the Archean-Proterozoic transition in the Bastar Craton, and this study is confined to the granites of Kanker pluton. Based on geochemical systematics, the Kanker granites are classified into sanukitoids, biotite and two-mica granites and hybrid granites. The compositional diversity of the Kanker granites is attributed to two end-member sources, i.e., the enriched mantle and an older felsic crust, and the interactions between them. The sanukitoids were derived from an enriched mantle source that was metasomatized by the subducted sediments. Heat supplied by the sanukitoid magmas induced the crustal melting to form the biotite and two-mica granites. The interaction between these two mutually end-member sources, i.e., the enriched mantle and an older felsic crust, resulted in the formation of hybrid granites. The evolution of the Kanker granites can be accounted for a transitional geodynamic environment, involving subduction and collisional tectonics during the Archean-Proterozoic transition.